Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Materi Ciri Makhluk Hidup melalui Implementasi Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) pada Siswa Kelas VI SDN 2 Rawa Laut, Bandar Lampung - Dentiana Saleh (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
Problem solving used in this study is to apply the Cooperative learning model type Team Assisted Individualization (TAI). This research is a classroom action research which consists of 3 cycles. The research subjects were teachers (researchers) and sixth grade students at SDN 2 Rawa Laut Bandar Lampung with a total of 28 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that: (1) The students' average scores increased. At the pre-cycle stage of 60.71; in the first cycle got a score of 65.00; increased in the second cycle to 71.79; and increased again in the third cycle to 76.43; (2) Mastery of student learning has increased. At the pre-cycle stage, student learning completeness is 35.7%; increased in the first cycle to 53.6%; increased in the second cycle to 67.9%; and again increased in cycle III to 85.7%. The conclusion of this study is that through the implementation of the Team Assisted Indovidualization (TAI) cooperative learning model, the quality of science learning material on the characteristics of living things in class VI students of SDN 2 Rawa Laut Bandar Lampung has increased.